Pain management in intensive care unit patients after cardiac surgery with sternotomy approach - Vilīte, Baiba; Strīķe, Eva; Rutka, Katrīna; Leibuss, Roberts (Acta medica Lituanica, 2019)
Background. Postoperative pain is a common problem among intensive care patients. Pain management includes pain assessment and documentation, patient care, and pharmacological treatment. Materials and methods. The study used a prospective, cross-sectional design. Nineteen intensive care nurses and 72 intensive care patients after cardiac surgery with sternotomy approach were studied. Toronto Pain Management Inventory was used to assess nurses and the 2010 Revised American Pain Society Patient Outcome Questionnaire was used to assess the patients. A research protocol was used to document pharmacological treatment data and Visual Analog Scale (VAS) pain measurements. The pharmacological therapy data was available for 72 patients, but patient satisfaction measurements were acquired from 52 patients. Results. Postoperative pain for intensive care patients after cardiac surgery is mostly mild (68.66%). Pain intensity had a tendency to decrease over time, from a mean VAS score of 4.66 two hours after extubation to a mean VAS score of 3.12 twelve hours after extubation. Mostly opioids (100%) and nonsteroidal anti‑inflammatory drugs (NSAIDs, 77.8%) were used for pharmacological treatment, and treatment was adjusted according to pain levels and patient needs. Patient satisfaction regarding pain management in the first 24 hours after surgery was high (94.2%), even though the nurses’ pain knowledge was average (X = 60.6 ± 7.3%). Conclusions. An individualized pain management plan requires pain documentation and ensures high patient satisfaction. Pain levels after cardiac surgery with sternotomy approach are mostly mild and patient satisfaction is high.